SeCRoP: secure cluster head centered multi‐hop routing protocol for mobile ad hoc networks. Issue 16 (4th July 2016) - Umar, Muhammad Muneer; Mehmood, Amjad; Song, Houbing
Abstract: Because of the absence of central control and limited capabilities of tiny nodes in mobile ad hoc networks (MANETs), these types of networks are always vulnerable to different kind of threats. Threats can be active and passive. Many cryptographic techniques are suggested for securing MANETs from various threats. This paper introduces a new method using cluster heads with cryptographic keys, for each node, in cluster‐based MANETs. Cluster heads are selected according to some definite criteria among the nodes in the clusters. Cluster heads keep the private keys for decryption while each member node is assigned a unique public key for encryption purpose. The approach is very flexible as it supports the nodes' migration to other clusters and transfer of control for one cluster head to another. Different scenarios are explained in the paper to tackle the security mechanism and nodes migration to other clusters. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This article introduces a new method using cluster heads with cryptographic keys, for each node, in cluster‐based MANETs. Cluster heads are selected according to some definite criteria among the nodes in the clusters. Cluster heads keep the private keys for decryption while each member node is assigned a unique public key for encryption purpose.